The analgesic effect of tramadol versus morphine in the treatment of cancer pain in National Cancer Institute, University of Gezira, Sudan (2018) - Ghazi Gasmalla Mohamed Ibrahim; Khalid Abbas Owish; Mohammed Suliman Zaroug (Open Journal of Pain Medicine - Peertechz Publications, 2021)
Cancer pain treatment following the World Health Organization guidelines is effective and feasible. However, the evidence supporting the use of opioids for mild to moderate pain on the Second step of the analgesic ladder is widely discussed. The present assessment compares the efficacy and safety of the use of tramadol in comparison to morphine in the treatment of cancer pain patients. This blind and random study was conducted at the National Cancer Institute at Gezira state in the period from April to October 2018. A total of 100 patients divided into two groups (50 patients for each group) were included in this study. In group one, the patients received tramadol whereas group two received oral morphine and the average dose was 5mg every 4 hours. On the other hand, the average dose of tramadol was 100mg every 6 hours. Our results showed that satisfaction from tramadol was 92%, in other words, 8% were not satisfied, and the most observed side effects were Nausea, Loss of appetite, and Dry mouth. However, morphine satisfaction was 90% while 10% was not satisfied and Nausea, Loss of appetite, and Dry mouth were the most side effects observed. In conclusion, results suggest that tramadol can be used in the treatment of cancer pain, as well as morphine with a slight advantage of tramadol over morphine for the lesser percentage of side effects compared to morphine.